Investigation on the impeller-diffuser interaction on the unstable flow in a mixed-flow pump using a modified partially averaged Navier-Stokes model. (15th October 2021) - Ye, Weixiang; Geng, Chen; Ikuta, Akihiro; Hachinota, Shinya; Miyagawa, Kazuyoshi; Luo, Xianwu
Abstract: In this paper, the effect of the impeller-diffuser interaction on the unstable flow in a mixed-flow pump operating under one part-load condition is investigated based on the local energy loss analysis using a modified SST k-ω partially averaged Navier-Stokes (MSST PANS) model. The comparison on the pump performance shows a good agreement between the experiment and simulation. The characteristic curve of the test pump presents a positive slope region, where hydraulic loss increases 90.75% in the impeller and 16.75% in the diffuser. The internal flow analysis depicts that the rotating stall evolution captured in the impeller passages involves larger energy transfer while the separating flow in the diffuser passage involves lower energy transfer. As the impeller blade tailing edge (TE) begins to interact with the diffuser blade leading edge (LE), the vortex attached to the impeller blade TE is cut off into two parts, one of which keeps propagating circumferentially and forms the rotating stall in the impeller, and the other is regarded as the shedding vortex, moving into the diffuser. Further analysis by the Fast Fourier Transform and proper orthogonal decomposition reveals the frequency of rotating stall is 1.49 f n, and the frequency of the shedding vortex is 0.53 f n . Highlights: Hydraulic loss is higher in the impeller than in the diffuser. Rotating stall evolution in the impeller involves with high energy transfer. Impeller-diffuser interaction is regarded as the "actuator" for the rotating stall evolution. Shedding vortex in the diffuser is separated from the rotating stall in the impeller.